Subgroup Decomposition in MathrmOut(F_{n}) - Handel, Michael (Memoirs of the American Mathematical Society Ser., 2020)
In this work the authors develop a decomposition theory for subgroups of \mathsf{Out}(F_n) which generalizes the decomposition theory for individual elements of \mathsf{Out}(F_n) found in the work of Bestvina, Feighn, and Handel, and which is analogous to the decomposition theory for subgroups of mapping class groups found in the work of Ivanov.